The Male Islamic Studies Teachers' Perceptions of the Extent of Including National Values in High School Courses - Alwadai, Mesfer Ahmed Mesfer; Alhaj, Ali Albashir Mohammed (Technium Social Sciences Journal, 2022)
The current research paper aims at exploring the male Islamic studies teacher's perceptions of the extent of including national values in high school courses. The researchers used the non-experimental research method to collect the study data. The results are based on a questionnaire conducted with 192 male Islamic studies teachers working in Saudi high schools. The study came out with important results among them are: there are valuable national values were included in Saudi high school courses and textbooks. The results also indicated that some of these national values were repeated in the content of these courses several times. In the light of those findings, the researchers recommend attention should be paid to adding more national values to the content reaping great benefits from the national values included and suggested in this study, and carrying out further research papers on the topic for other stages of courses at elementary schools, colleges and the like.